Влияние наноструктурированных порошков-модификаторов на структуру сварного шва; Известия вузов. Физика; Т. 56, № 7-2 - Кузнецов М. А. Максим Александрович; Журавков С. П. Сергей Петрович; Зернин Е. А. Евгений Александрович; Колмогоров Д. Е. Дмитрий Евгеньевич; Яворовский Н. А. Николай Александрович (2013, 2013)
Заглавие с экрана